ANALISIS KEMAMPUAN BERPIKIR GEOMETRI BERDASARKAN TAHAP BERPIKIR VAN HIELE PADA PEMBELAJARAN MATEMATIKA SISWA SMP - Aulidia Nauval Kurnia; Nita Hidayati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
Geometry is a mathematical branch that deals with the shape of an object, the spatial relationship between various objects, and its properties. Learning geometry is essential to supporting logical thinking ability, perceptual intuition, and reading and interpreting mathematical arguments. But many middle school students do not reach the stage of deduction and precision. The research was to analyze a high school student's geometry ability based on Van Hiele's stages of thinking. They consist of five levels of visualizing, analysis, sequence, deduction, and precision. It is a type of qualitative study with a descriptive method. The sample consisted of 20 eighth-graders in the located in the Karawang district. Data collection is carried out using a written questionnaire and test. Research shows that stage-0 (visualization) is the student's most achievable point from a questionnaire at 55% and a written test of 65%. The third stage (deduction) and fourth (accuracy) are the most difficult for students to achieve, based on written tests only 9% of students reach the third stage and only 6% of students reach the fourth. Student difficulties in learning this geometry may be due to several factors in their understanding of prerequisite materials, ability to concepts and pale-building qualities is lacking, and limited skill in using geometry ideas to solve mathematical problems.